Digitization of Muhammadiyah Education: Opportunities and Challenges in Creating Access to Inclusive Education - Huwaidah, Devi Azalia Fitriabil; Dartim, Dartim (Universitas Muhammadiyah Surakarta, 2025)
The advancement of global digital technology has driven fundamental changes in the education sector, thus demanding the adaptation of all elements of society to remain relevant in the era of disruption. In this context, Muhammadiyah as an Islamic movement that focuses on da'wah, education, and health has a strategic role in bridging the digital divide in Indonesia, especially in the education sector. Although internet penetration in Indonesia continues to increase, digital inequality still occurs, especially in the 3T area, which has an impact on the quality of education in Muhammadiyah schools. This research aims to identify opportunities and challenges in the implementation of digitalization of Muhammadiyah education, with an emphasis on the success of digitalization and inclusive education policies. Based on a qualitative descriptive literature study, it was found that the success of digitalization is greatly influenced by technological readiness, equitable distribution of infrastructure, and human resource competence. Digitalization also has the potential to improve accessibility and quality of learning through the use of digital platforms that are more personalized, collaborative, and interactive. The main challenges faced include infrastructure inequality and limited digital skills of educators, especially in remote areas. Therefore, the strategy to optimize the digitization of Muhammadiyah education needs to include infrastructure improvement, continuous training for teachers, and collaboration with the government and the private sector to build an inclusive and quality digital education ecosystem.